Polymer modified bitumen: review - Pyshyev, Serhiy; Gunka, Volodymyr; Grytsenko, Yuriy; Bratychak, Michael (Publishing House of Lviv Polytechnic National University, 2016)
The main reasons and ways of bitumen modification by polymers were examined. Positive and negative aspects of the usage of different polymer modifiers (elastomers, thermoplastic elastomers, reactive polymers, thermoplastics) were analysed. The authors’ achievements concerning modification of bitumen by various polymers, namely indene-coumarone, petroleum, phenol-formaldehyde and epoxy resins, were described. У статті розглянуті основні причини та способи модифікації бітумів полімерами. Проаналізовано позитивні і негативні сторони використання різних груп полімерних модифікаторів (еластомери, термопластичні еластомери, реакційні полімери, термопласти). Описано досягнення авторів статті в області модифікації бітумів полімерами: інден-кумароновою, нафтополімерними, фенол-формальдегідними і епоксидними смолами.
Полімер-модифіковані бітуми: огляд
Keywords: polymer modified bitumen; elastomer; thermoplastic elastomer; reactive polymer; thermoplastic; полімер-модифікований бітум; еластомери; термопластичні еластомери; реакційні полімери; термопласти